Profile of Mathematical Reasoning Ability of Students of SMK Ma'wataibin Pagelaran in Solving Problems of Arithmetic Rows and Rows - Fitri Handayani, Ucik; Cahya Setiawati, Risma (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This study describes the profile of students' mathematical reasoning ability in solving arithmetic rows and series problems. Based on the results of observations and interviews with the mathematics teacher of class X SMK Ma'wataibin Pagelaran Malang, information was obtained that 83% of students in the class tended not to be able to conclude the answer. This descriptive research uses a qualitative approach. The sample of this research is 19 students of class X SMK Ma'wataibin Pagelaran. They then selected one each in the high, medium, and low-level categories. Then, interviews were conducted with each subject to explore deeper information. The test instrument used is 1 question that contains four indicators of mathematical reasoning ability. The test results obtained that students in the high mathematical reasoning ability category amounted to 7 students, with a percentage of 36.85%. Students in the moderate mathematical reasoning ability category amounted to 8 students, with a rate of 42.10%. Students in the low mathematical reasoning ability category amounted to 4 students, with a rate of 21.05%. Based on the results of the data analysis, it is shown that high-category students fulfill four indicators of reasoning ability according to their abilities. Medium-category students correctly fulfill three indicators of mathematical reasoning ability: writing conjectures, doing work, and providing reasons/evidence. Low-category students only fulfill one indicator of mathematical reasoning ability, namely writing conjectures.